2020
DOI: 10.1103/physrevb.101.014202
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hermitian disorder in two-dimensional optical lattices

Abstract: In this paper, we study the properties of two-dimensional lattices in the presence of non-Hermitian disorder. In the context of coupled mode theory, we consider random gain-loss distributions on every waveguide channel (on site disorder). Our work provides a systematic study of the interplay between disorder and non-Hermiticity. In particular, we study the eigenspectrum in the complex frequency plane and we examine the localization properties of the eigenstates, either by the participation ratio or the level s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 103 publications
3
61
0
Order By: Relevance
“…Similar to Ref. 16 we found that eigenvalues near the rectangular border of the complex spectrum correspond to more localized states. Therefore, to deal with eigenvalues with similar localization properties we calculated r of 25% smallest-modulus eigenvalues selected by a rectangular window whose sides are roughly twice smaller than the whole spectrum.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Similar to Ref. 16 we found that eigenvalues near the rectangular border of the complex spectrum correspond to more localized states. Therefore, to deal with eigenvalues with similar localization properties we calculated r of 25% smallest-modulus eigenvalues selected by a rectangular window whose sides are roughly twice smaller than the whole spectrum.…”
supporting
confidence: 89%
“…A simple and elegant extension of the 2D Anderson localization problem was proposed in a recent paper by Tzortzakakis, Makris and Economou (TME) 16 . They studied 50 × 50 tight-binding square lattices with real overlap energy I ij = I, and random complex onsite energies E i whose real and imaginary parts are independent random variables distributed uniformly between −W/2 and W/2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The non-Hermitian Anderson Hamiltonian [26,27] H = −∇ 2 + V 1 (r) + iV 2 (r) (16) has been studied in the context of a random laser [28]: a disordered optical lattice with randomly varying absorption and amplication rates, described by a complex dielectric function V 1 + iV 2 . On a d-dimensional square lattice (lattice constant a), the discretization of −∇ 2 → a −2 d i=1 (2−2 cos k i a) produces a spectral band width of W 0 = 4d/a 2 .…”
Section: Introduction -mentioning
confidence: 99%
“…The spectral statistics of random Hermitian Hamiltonians usually exhibits universal behavior, depending only on symmetries of the system [68]. An interesting question then naturally arises whether the spectral statistics of disordered non-Hermitian Hamiltonians also exhibits universal behavior [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%